Hot water disinfection treatment to eliminate Neonectria ditissima latent infections in apple scion wood - Amponsah, N.T.; Walter, B.M. Fisher M.; Frijters, L.; Hedderley, D.I.; Scheper, R.W.A. (New Zealand Plant Protection, 2016)
The European canker pathogen Neonectria ditissima can be transmitted by apple scion wood into newly developing trees following grafting or budding resulting in disease development and progression An in vitro hot water treatment showed that both conidia and mycelium of N ditissima can be killed when placed into water at 50C for 8805; 5 min However diseased scion wood required 8805; 15 min disinfection at the same temperature to eliminate all internal pathogens including N ditissima At this temperature and time duration no mycelium growth was observed after 2 weeks incubation of cut pieces of the disinfected tissues on apple sap amended water agar Although the treatment was 100 effective at eliminating some identified and nonspecific pathogens visual assessment of both the scion and rootstock viability and vigour six months after the hot water treatment showed that 98 of the rootstocks and scions failed to grow and develop